Archaebacterial DNA-dependent RNA polymerases testify to the evolution of the eukaryotic nuclear genome. - Pühler, G (1989)
Genes for DNA-dependent RNA polymerase components B, A, and C from the archaebacterium Sulfolobus acidocaldarius and for components B", B', A, and C from the archaebacterium Halobacterium halobium were cloned and sequenced. They are organized in gene clusters in the order above, which corresponds to the order of the homologous rpoB and rpoC genes in the corresponding operon of the Escherichia coli genome. Derived amino acid sequences of archaebacterial components A and C were aligned with each other and with the sequences of corresponding (largest) subunits from the archaebacterium Methanobacterium thermoautotrophicum, with sequences of various eukaryotic nuclear RNA polymerases I, II, and III, and with the sequence of the beta' component from E. coli polymerase. The archaebacterial genes for component A are homologous to about the first two-thirds of genes for the eukaryotic component A and the eubacterial component beta', and the archaebacterial genes for component C are homologous to the last third of the genes for the eukaryotic component A and the eubacterial component beta'. Unrooted phylogenetic dendrograms derived from both distance matrix and parsimony analyses show the archaebacteria are a coherent group closely related to the eukaryotic nuclear RNA polymerase II and/or III lineages. The eukaryotic polymerase I lineage appears to arise separately from a bifurcation with the eubacterial beta' component lineage.